Unordered Love in infinite directed graphs - Peter D. Johnson (International Journal of Mathematics and Mathematical Sciences)
A digraph D=(V,A) has the Unordered Love Property (ULP) if any two different vertices have a unique common outneighbor. If both (V,A) and (V,A−1) have the ULP, we say that D has the SDULP.